(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Shatt Al Hilla River within Babylon Governorate is one of the main water resources in Hilla citys which uses for different purposes. The object of this paper is studying the quality of surface water resources in the study area besides determining its suitability for different anthropogenic uses and classifying the water type. This study included the analysis of (9) surface water samples along the river, those analyses included chemical parameters such as (Ca2+, Mg2+, Na+, K+) and main anions (HCO3=, CO3=, SO42-, Cl-) and other important anions, i.e. Nitrate (NO3=) and (PO43-), Total Hardness, Electrical Conductivity, Total Dissolved Salts. Results of Water quality index ranged from good to excellent type, Piper Diagram referred to water of class (c) which means the water of Earth Alkaline source with increasing in portions of Alakalis under prevailing sulfate and Chloride. Water suitability conducted by comparing with World health organization standers and Iraqi standers, the result of water suitable for different uses (drinking, irrigation, livestock, building purposes) except for industrial uses because of the high concentrations of the chemical parameters.